Characteristics of Optimized Al:ZnO sputtering targets prepared by nanostructured powder. Issue 5 (1st April 2020) - Liu, Haichao; Gao, Ming; Yang, Benrun; Chen, Haojie; Zhang, Huarui; Zhang, Hu
Abstract: Optimized Al:ZnO sputtering target was prepared by cold isostatic pressing (CIP) using nanostructured zinc oxide powder and aluminum oxide powder as raw material. Compared with the target prepared by conventional raw materials, the performance of the optimized Al:ZnO sputtering target is greatly improved. The microstructure of the optimized Al:ZnO sputtering target is refined and its average grain size is less than 5 μm with 99.7% theoretical density. Al:ZnO thin films of both optimized and conventional targets were prepared by RF magnetron sputter and their properties were characterized, respectively. The Al:ZnO thin films obtained by optimized target feature better uniformity and compactness, and the internal stress is −378.8 MPa, which is nearly 2/3 lower than that of the conventional target. The film obtained by optimized targets also features a 97% IR transmittance, 1.71 nm Rq surface roughness and non-offset (002) XRD peak. It can be speculated that the optimized Al:ZnO target has great potential to prepare micrometer scale Al:ZnO films and employed in thin-film ZnO device industry.